Waves due to initial disturbances at the inertial surface in a stratified fluid of finite depth - Prity Ghosh; Uma Basu; B. N. Mandal (International Journal of Mathematics and Mathematical Sciences)
This paper is concerned with a Cauchy-Poisson problem in a weakly stratified ocean of uniform finite depth bounded above by an inertial surface (IS). The inertial surface is composed of a thin but uniform distribution of noninteracting materials. The techniques of Laplace transform in time and either Green's integral theorem or Fourier transform have been utilized in the mathematical analysis to obtain the form of the inertial surface in terms of an integral. The asymptotic behaviour of the inertial surface is obtained for large time and distance and displayed graphically. The effect of stratification is discussed.